Z39.50 Unzipped - Ghosh, Saptarshi (Journal of Information and Knowledge, 2002)
This paper attempts to describe, in layman’s terms, the underlying principles behind the Z39.50 standard. The libraries in Europe and America use the standard. From the mass of literature available over INTERNET the basic elements of the protocol have been ripped i.e. what it is, how it works and how it fulfils the need for interoperable information retrieval. It also shows the new standards like XML (Extensible Markup Language), and RDF is being used in conjunction with it.